Understanding disability : a lifespan approach - Quinn, Peggy (Sage sourcebooks for the human services series ;, 1998)
Understanding Disability details expected developmental stages for those without disabilities as well as the impact of disability at each of these periods. This is a much needed reference for working with a person with a disability, or with a family member or other interested party.